The Roads that led to Edinburgh - Inglis, Harry (Proceedings of the Society of Antiquaries of Scotland, 1916)
The investigation of early roads is hampered by the absence of early road maps, as the first of any real service were those of Adair, issued as late as 1680. At an earlier date information derives from travellers narratives and early documents, which identify their existence without specifying their position. The making of new roads in the last few hundred years has in many instances led to these old routes being abandoned. The article considers early maps and documentary references going back to the Roman period, the first surveys of Scotland, the military survey of Scotland, evidence for old population centres, Roman roads, the roads from Berwick, Kelso, Jedburgh, Hawick and Selkirk, Peeble, Biggar, Lanark, Hamilton and Glasgow in addition to the roads going out of Edinburgh.